Update Treatment for Prolactinoma - María Margarita, Chávez Hernández; María Valeria, Jiménez Báez; María Fernanda, Armijo Medina; Jorge Miguel, Domínguez Leyva; Alejandra, Góngora Valencia Karen; Karen Alejandra, Góngora Valencia; Sergio Geovanni, Guerra Rentería; Jurado Luis, Sandoval (International Journal of Innovative Research in Medical Science, 2018)
Prolactinomas are the most common type of functional pituitary tumor. The present manuscript is an update on the treatment modalities for prolactinomas. Effective hyperprolactinemia treatment is of great importance, due to its potential deleterious effects including infertility, gonadal dysfunction and osteoporosis. Dopamine agonist therapy is the first line of treatment for prolactinomas; recurrence of disease after cessation of the drug may occur in patients. Its safety profile remains high, allowing its use during pregnancy.